1,2-Bis(4-Pyridyl) Ethane Catalysed Oxidative Conversion of D-Lactose to Lactobionic Acid by Cr(VI) in Aqueous Acetic Acid Medium: A Kinetic and Mechanistic Study: Life Sciences-Chemistry - Vijaya, J.; Dharmaraja, J.; Raj, V.; Harikrishnan, B. (International Journal of Life Science and Pharma Research, 2022)
The kinetics of oxidation reactions and the investigations of the reaction mechanisms from the kinetic data have been always the more interesting in the chemical research and industrial applications. The kinetics of oxidation of sugars has been a subject of extensive research in recent years. The biological as well as the economic importance of carbohydrates is responsible for the great interest in the study of their bio- and physio -chemical properties. The kinetics of oxidative degradation of different sugars by metal ions including Cr (VI) has been studied under different conditions. Chomium (VI) compounds are powerful oxidants at low or neutral pH as well as Cr (VI) is a well-known oxidant in acetic media. Aim of our present investigation deals with oxidation of D-Lactose using Cr (VI) Oxidizing agent, Trimethylammonium fluorochromate [TriMAFC] which was carried out in protic solvent as a medium at 308 K in the presence of 1,2-bis(4-pyridyl)ethane as a catalyst . The oxidation of D-Lactose yields the corresponding aldonic acid and Cr3+ as final products. Lactobionic Acid (LBA) has been used for food and pharmaceutical applications. Thus the kinetics and mechanism of carbohydrates using Cr (VI) as oxidant, 1,2-bis(4-pyridyl)ethane as a catalyst is very important from biochemical and kinetic viewpoints. Our experimental studies showed that reaction progressed with first order kinetics with respect to [TriMAFC], [1,2-bis(4-pyridyl)ethane] and [H+] with the fractional Order dependence on [DLactose]. It was found that introduction of sodium perchlorate results in decrement of the reaction rate substantially. The rate constant increased with increase in the concentration of perchloric acid. Also, the rate of reaction decreases with increasing the concentration of acetic acid. For acrylonitrile, no polymerization occurs. The reaction was carried out at four different temperatures to determine the activation parameters. An appropriate mechanism was suggested based on the observed kinetic effects.